Refinement of Kneser theorem on zeros of solutions of the equation $y" + p(x)y = 0$ - Slyusarchuk, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We find conditions for a linear homogeneous second order equation to be nonoscfflatory on the half-axis and such that its solutions have infinitely many zeros.